Use Of The Circle-Segments Method As A Data Visualization Tool For An Artificial Neural Network. - Shir, Li Wang; Chee, Peng Lim; Abdul Aziz, Zalina (2006)

(untitled)
Process modeling and prediction is one of the major tasks in many industrial applications. The Multi- Layered Perceptron (MLP) neural network has been a popular approach in process modeling and prediction, and has produced good results.